The Role of Local Budget Transparency in Community Participation in Tanjungpinang: Peran Transparansi Anggaran Daerah terhadap Partisipasi Masyarakat di Tanjungpinang - Aisyah Ainayatul Hikmah; Putri Maharani Aisyah; Selvi Ega Sari (Academia Open, 2025)
Background: Transparency in regional budgeting serves as an essential foundation for accountable governance and encourages public involvement in financial oversight. Specific background: In Tanjungpinang, the regional government has provided budget information through digital platforms to support public access to planning and expenditure documents. Knowledge gap: Despite the availability of this information, community participation is not yet optimal due to varied levels of fiscal literacy, limited technological access, and insufficient outreach. Aims: This study examines how regional budget transparency is implemented in Tanjungpinang and how accessible budget information corresponds with community participation. Results: The findings show that while budget documents are available online, public use remains limited. Low financial understanding, irregular data updates, and digital access barriers reduce community involvement, with higher participation found among groups with stronger digital access and education. Novelty: This research offers contextual evidence from a region with diverse literacy levels, illustrating that transparency alone does not ensure active participation. Implications: Strengthened public outreach, clearer information presentation, and improved fiscal literacy are essential to support more inclusive community participation in regional budgeting. Highlights Public use of regional budget information in Tanjungpinang remains limited. Fiscal literacy and digital accessibility shape levels of community participation. Enhanced outreach and clearer information delivery support broader public involvement. Keywords Budget, Region, Transparency, Community, Participation